Is the neutrophil/lymphocyte rate as effective as CURB-65 in the patient management of the community-acquired pneumonia patients admitted to the Emergency Medicine? - Barut, İlker and Yüksel, Melih and Kaya, Halil and Engindeniz, Zülfi (The European Research Journal, 2021)
Objectives: The aim of this study was to identify the patients with community-acquired pneumonia (CAP) in emergency departments, and to compare CURB-65 scoring system and Neutrophil/Lymphocyte Ratio (NLO) which are some of the commonly used blood parameters to make an inpatient or outpatient decision quickly and effectively. Methods: This study was performed retrospectively by examining the files of 442 patients who were admitted to the adult emergency department of Bursa Yüksek İhtisas Training and Research Hospital between September 1, 2017 and October 31, 2018. The demographic characteristics, physical examination findings, laboratory results, hospitalizations, and CURB-65 scores of the patients included in the study were recorded on a pre-prepared paper and electronic form and statistical analyzes of these data were conducted. Results: Two hundred and fifty-five (57.69%) patients were male and the mean age was 70.93 years. The mean NLO value was 9.85, the mean MPV value was 8.62, the mean eosinophil value was 0.15 and the mean CURB-65 score was 1.85. When the post hoc paired group comparison was conducted for the mean NLR, it was found that the other groups differed from each other except the groups admitted to the intensive care unit and the service. Glasgow Coma Scale score and CURB-65 score were found to be significant predictors for hospitalization to service and intensive care unit (p < 0.05). Conclusions: We think that NLR may be useful in decision-making process, especially in prospective studies, although the use of NLR in patients with CAP is not statistically significant. In this study, we also examined that CURB-65 is an effective scoring system in the management of this patient group.